Can larvae of a marine fish adapt to ocean acidification? Evaluating the evolutionary potential of California Grunion (Leuresthes tenuis). (31st December 2018) - Tasoff, Alexander J.; Johnson, Darren W.
Abstract: Ocean acidification can reduce the growth and survival of marine species during their larval stages. However, if populations have the genetic capacity to adapt and increase their tolerance of low pH and high p CO2 levels, this may offset the harmful effects of ocean acidification. By combining controlled breeding experiments with laboratory manipulations of seawater chemistry, we evaluated genetic variation in tolerance of ocean acidification conditions for a nearshore marine fish, the California Grunion ( Leuresthes tenuis ). Our results indicated that acidification conditions increased overall mortality rates of grunion larvae, but did not have a significant effect on growth. Groups of larvae varied widely with respect to mortality and growth rates in both ambient and acidified conditions. We demonstrate that the potential to evolve in response to ocean acidification is best described by considering additive genetic variation in fitness‐related traits under both ambient and acidified conditions and by evaluating the genetic correlation between traits expressed in these environments. We used a multivariate animal model to estimate additive genetic (co)variance in larval growth and mortality rates under both ambient and acidified conditions (low pH/high p CO2 ). Our results suggest appreciable genetic variation in larval mortality rates ( h 2 Ambient  = 0.120; h 2 Acidified  = 0.183; rG  = 0.460), but less genetic variation in growth ( h 2 Ambient  = 0.092; h 2 Acidified  = 0.101; rG  = 0.135). Maternal effects on larval mortality rates accounted for 26%–36% of the variation in phenotypes, but maternal effects accounted for only 8% of the variation in growth. Collectively, our estimates of genetic variation and covariation suggest that populations of California Grunion have the capacity to adapt relatively quickly to long‐term changes in ocean chemistry.